(untitled) (Research, Society and Development, 2020)
Cookies, in general, are well accepted by all audiences, and research and investments in this type of product are of great importance to meet market demands. There are few product options for people with gluten intolerance on the market, and rice flour and babassu fruit mesocarp flour are good options for the development of new products for this audience. The objective of the present work was to prepare a gluten-free sweet biscuit with high nutritional value, based on babassu mesocarp flour with partial replacement by rice flour, to carry out the physical-chemical, microbiological characterization, sensory acceptance, and purchase intention of consumers. Three different formulations were studied, with 50, 75 and 100% babassu fruit mesocarp flour. Physical-chemical analyzes of moisture, water activity, ash, lipids, proteins and carbohydrates (by difference) were carried out, the microbiological quality was also evaluated according to the legislation and sensory acceptability through a questionnaire with 80 untrained tasters, as for the appearance, color, aroma, texture, sweetness, flavor, global impression and purchase intention attributes. The results showed that the cookies with variations of babassu fruit mesocarp flour and rice flour are comparable to other studies found in the literature, in terms of physical-chemical and microbiological characteristics. In the sensory evaluation, the cookies received grades in the acceptance range for all formulations, demonstrating that the product has the potential to be in the market.